Economics of Nepalese Telecom Industry - Pokhrel, Rajendra Kumar (Tribhuvan University Journal, 2022)
This paper aims to investigate the economics of Nepalese telecom industry with special reference to Nepal Telecom. The study is undertaken with the objectives to analyze Nepal Telecom as the market leader, drive an aggressive pricing model and to explore reliable telecommunication service in Nepal and become the lowest cost provider. Telecommunication at present, is the transmission of information, voice or data per time and space through electronic device. Efficiency gains and cheaper phone calls are possible from telecommunications aggressive pricing and effective customer care. The telecommunications revolution has arrived to 21st century wireless communication with fiber to the home (FTTH), 4G and 5G. The overall telecommunication market is huge. Majority of market share is needed to become a market leader. Telecom management need to formulate effective plan to achieve the target within the period of five years. Fiber to the home (FTTH) service, which includes three in one as voice, internet and IPTV has been expanded within 62 districts. Nepal Telecom has been able to expand 4G network in all 77 districts of the country with the wide coverage of 654 local bodies and 85% of the total population. FTTH is an important project as it supports the fifth-generation mobile internet (5G) which is coming to Nepal in the near future.